Desperately seeking Susan - Arquette, Rosanna; Madonna; Quinn, Aidan
A bored suburban housewife, seeking adventure to her life, accidentally gets hit on the head, wakes up with amnesia, and is mistaken for a free-spirited New York City drifter named Susan.